MENYOAL PEMBELAJARAN SAINS DI SEKOLAH: BAGAIMANA SEHARUSNYA? - Djudin, Tomo (Universitas Tanjungpura, 2010)
Teachers understanding on the nature of science will determine types of students learning activities in the class. In designing a science teaching-learning process meaningfully, a teacher should consider and pay attention to the learning activities. They are (1) logical plane activities; (2) evidental or experiental plane activities; (3) psychological plane activities. A science text-books centered teaching should be modified because, the students comprehension about science products (concept and principles) could not be developed meaningfully by using text-books only. This culture is also contrary with the nature of science and is not able to build a science and technology literate people.Key words: Teachers understanding; learning activities